Analysis of Textbooks on Trigonometric Identity Equations in the 1975 Curriculum, Merdeka Curriculum, and the 2nd Blitzer Trigonometry Book - Ely Susanti, Ely; Hiltrimartin, Cecil; Okta, Miko (Universitas Negeri Makassar, 2025)
This study aims to analyze the presentation of trigonometric identities in three textbooks used in different curricula, namely Mathematics 7 for Senior High School (1975 Curriculum), Mathematics for Senior High School/Vocational High School Grade XI Independent Curriculum (2022), and Trigonometry (2nd Edition) by Blitzer (2018). The research method uses content analysis of facts, concepts, principles, and examples of questions and problem-solving questions in these books. The results of the analysis show differences in presentation approaches, where the 1975 Curriculum book presents material in a simple but less systematic manner, the Independent Curriculum combines context but is less consistent, and the Blitzer book presents comprehensive material with a focus on real-world applications. Analysis of questions based on cognitive levels and the PISA framework places the Blitzer book as superior in terms of the variety and depth of questions. These findings are important as material for evaluating and developing textbooks to improve understanding and competitiveness of mathematics education at national and international levels.